The Paradox Hotel : [large type] a novel - Hart, Rob (Fiction writer) (Thorndike Press large print core series., 2022)
"January Cole's job just got a whole lot harder. Not that running security at the Paradox was ever really easy. Nothing's simple at a hotel where the ultra-wealthy tourists arrive costumed for a dozen different time periods, all eagerly waiting to catch their "flights" to the past. Or where proximity to the timeport makes the clocks run backward on occasion--and, rumor has it, allows ghosts to stroll the halls. None of that compares to the corpse in room 526. The one that seems to be both there and not there. The one that somehow only January can see. On top of that, some very important new guests have just checked in. Because the U.S. government is about to privatize time-travel technology--and the world's most powerful people are on hand to stake their claims. January is sure the timing isn't a coincidence. Neither are those "accidents" that start stalking their bidders. There's a reason January can glimpse what others can't. A reason why she's the only one who can catch a killer who's operating invisibly and in plain sight, all at once. But her ability is also destroying her grip on reality--and as her past, present, and future collide, she finds herself confronting not just the hotel's dark secrets but her own. At once a dazzlingly time-twisting murder mystery and a story about grief, memory, and what it means to--literally--come face-to-face with our ghosts, The Paradox Hotel is another unforgettable speculative thrill ride from acclaimed author Rob Hart"--